2005
DOI: 10.1111/j.1475-1313.2005.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity and limitations of the Nidek NT‐4000 non‐contact tonometer: a clinical study

Abstract: Using Goldmann applanation tonometry (GAT) as a gold standard, we evaluated the accuracy of Nidek NT-4000 pneumotonometry (NPT) in adults without corneal disease. Bland and Altman analysis of serial intra-ocular pressures (IOPs) measured with NPT and GAT in 10 healthy subjects revealed that the repeatability coefficients for the two methods were similar. NPT, GAT and ultrasonic pachymetry were then performed in 100 patients. Bland and Altman analysis showed that NPT yielded significantly higher readings than G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
17
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 17 publications
9
17
1
Order By: Relevance
“…Several studies compared the reproducibility and reliability of IOP measurements obtained with NCT, DCT, and GAT. [21][22][23][24] In most of these studies, similar reproducibility and reliability were demonstrated with all three devices. In this study, however, the results indicated better reproducibility of measurements for NCT, DCT, and GAT without a contact lens than with one.…”
Section: Discussionmentioning
confidence: 77%
“…Several studies compared the reproducibility and reliability of IOP measurements obtained with NCT, DCT, and GAT. [21][22][23][24] In most of these studies, similar reproducibility and reliability were demonstrated with all three devices. In this study, however, the results indicated better reproducibility of measurements for NCT, DCT, and GAT without a contact lens than with one.…”
Section: Discussionmentioning
confidence: 77%
“…A few techniques, including limbal pneumatonometry 5 and noncontact tonometry, 4 have been suggested as reliable alternatives for IOP measurements in diseased corneas. To our knowledge, we are unaware of any reports investigating these techniques in eyes implanted with keratoprostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Various alternatives, including tactile estimation, have been suggested, but these require the use of special implants and/or measuring techniques that are not practical in the office setting. [1][2][3][4][5] Additionally, various disease states, including acromegaly, corneal edema, and keratoconus, produce surface and/or thickness irregularities that undermine the accuracy of IOP measurements. 6 Presently, corneal pneumatonometry is an acceptable alternative when dealing with diseased or irregular corneas, where mire distortion precludes the accuracy of Goldmann applanation tonometry (GAT).…”
mentioning
confidence: 99%
“…An optical detector measures the change in light reflected from the corneal surface and correlates the change to IOP [48 ]. Several studies have found that NCT is significantly affected by CCT.…”
Section: Definitions Of Terminology Relevant To Corneal Biomechanicsmentioning
confidence: 99%